The Printed Reader : Gender, Quixotism, and Textual Bodies in Eighteenth-Century Britain - Dale, Amelia (Book collections on Project MUSE., 2019)
"The Printed Reader explores the transformative power of reading in the eighteenth century, and how this was expressed in the fascination with Don Quixote and in a proliferation of narratives about quixotic readers, readers who attempt to reproduce and embody their readings. The collection brings together key debates concerning quixotic narratives, print culture, sensibility, empiricism, book history, and the material text, connecting developments in print technology to gendered conceptualizations of quixotism"--